Fabrication of Au-In2O3 Thin/Thick-Film Gas Sensors and Their Sensing Characteristics for Toxic Gases - 김인호; 박은덕; 김한수; 한상도 (센서학회지, 2024)
This paper reports on highly sensitive and selective Au- In2O3 thin- and thick film gas sensors for detecting and measuring toxic gases. The used thin film was deposited on an alumina substrate using a high-frequency sputtering method, the sensor substrate with platinumheater and gold electrode was formed by screen printing, and the nano-catalyst material Au was deposited by thermal vapor deposition. The thick-film gas sensor was fabricated by screen printing using Au- In2O3 paste, and the sensor was finalized by annealing in air at800o C. The target toxic gases used were acetaldehyde, dimethyl disulfide, and 2-methyl-1-propanol. The fabricated thin-film gas sensorsshowed excellent sensitivity to dimethyl disulfide, and the thick-film gas sensors showed a strong response to acetaldehyde. In particular,the thin-film sensors annealed at 800o C exhibited excellent sensing characteristics such as high sensitivity, fast recovery, stability, andlinearity. Based on the surface oxidation reaction and electron transfer mechanism of the Au- In2O3 system, a sensing reaction mechanismand surface energy band model for 2-methyl-1-propanol were proposed.
Keywords: Gas sensor; Toxic gas; Au-In2O3; Thin-thick film; Sputtering; Thermal evaporation